Influence of impurities on the dynamics and synchronization of coupled map lattices - Jousseph C.A.C. (2003)
The influence of impurities and defects on the dynamics and synchronization of coupled map lattices (CML) is studied. In the context of CML we define impurities as sites in the lattice which have another local dynamics that from the whole lattice and defects as sites in the lattice without any dynamics. We show that synchronization and spatial intermittence are obtained as a function of the number of impurities present on a one-dimensional lattice. We also derive an analytical condition for a signal to "transpose" an impurity. For open flow models, we show that not only the presence of the impurity but also its position along the lattice and its local dynamics can be used to manipulate the lattice in order to obtain a regular or irregular motion. We also show how defects can be used to store information in a lattice. © 2003 Elsevier Science B.V. All rights reserved.